2009
DOI: 10.1093/aob/mcn244
|View full text |Cite
|
Sign up to set email alerts
|

Causes of decreased photosynthetic rate and metabolic capacity in water-deficient leaf cells: a critical evaluation of mechanisms and integration of processes

Abstract: With progressive WD, A decreases as g(s) falls. Under low light during growth and WD, A is stimulated by elevated CO(2), showing that metabolism (A(pot)) is not impaired, but at high light A is not stimulated, showing inhibition. At a given intercellular CO(2) concentration (C(i)) A decreases, showing impaired metabolism (A(pot)). The C(i) and probably chloroplast CO(2) concentration (C(c)), decreases and then increases, together with the equilibrium CO(2) concentration, with greater WD. Estimation of C(c) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

30
559
3
21

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 720 publications
(613 citation statements)
references
References 131 publications
30
559
3
21
Order By: Relevance
“…Wong et al (1979) showed that P i remained constant whilst A and g s varied together, and that stomatal aperture is determined by the capacity of the mesophyll tissue to fix carbon. Our results could therefore be a reflection of direct effects of leaf water status on A mediated via non-stomatal (metabolic) limitations that are independent of P i (Lawlor & Tezara, 2009). Furthermore, it has been demonstrated that C 4 plants are sensitive to non-stomatal limitations mediated via plant water status, and the effect was greater than in C 3 leaves (Ripley et al, 2007;Taylor et al, 2011).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Wong et al (1979) showed that P i remained constant whilst A and g s varied together, and that stomatal aperture is determined by the capacity of the mesophyll tissue to fix carbon. Our results could therefore be a reflection of direct effects of leaf water status on A mediated via non-stomatal (metabolic) limitations that are independent of P i (Lawlor & Tezara, 2009). Furthermore, it has been demonstrated that C 4 plants are sensitive to non-stomatal limitations mediated via plant water status, and the effect was greater than in C 3 leaves (Ripley et al, 2007;Taylor et al, 2011).…”
Section: Discussionmentioning
confidence: 79%
“…This response limits transpiration rates and also CO 2 supply to the mesophyll which, in turn, can reduce A (Bunce, 2006). Photosynthesis is also very sensitive to the direct effects of leaf water deficits measured as more negative W leaf (Lawlor and Tezara, 2009). Therefore, improvements in W leaf at post-glacial compared to glacial pCO 2 in this study indicate that plant water status was more favourable for carbon assimilation, and are consistent with studies finding that leaf W leaf and A are improved under elevated pCO 2 in both C 3 and C 4 plants under water deficits (Wall, 2001;Wall et al, 2001;LeCain et al, 2003;Robredo et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In the initial stages of water stress, a decrease in stomatal conductance mediated by ABA can limit the internal CO 2 concentration used in C assimilation (Zhang and Davies, 1990;Tardieu and Davies, 1993). As the stress progresses, the decrease in photosynthetic activity and the continuation of respiration both contribute to the maintenance (or increase) of internal CO 2 in plants subjected to stress (Lawlor and Tezara, 2009). Our results support this concept.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased chlorophyll is recognized to directly affect photosynthesis which plays a vital role in plant growth and development (Chaves et al 2009;Flexas et al 2004;Lawlor and Tezara 2009). Larger fall in the chlorophyll content of J. pentantha may depict its susceptibility to water deficit.…”
Section: Discussionmentioning
confidence: 99%